Perancangan Aplikasi Jadwal dan Laporan Kunjungan Kerja pada Bappelitbang (International Forum of Researchers and Lecturers, 2025)
The Planning, Research, and Development Agency (BAPPELITBANG) has an important role in supporting regional development planning and evaluation. One of the main activities of this agency is the coordination of working visits with external agencies or institutions. The process of managing schedules and work visit reports is currently still carried out manually, causing obstacles such as delays in information, duplicate schedules, and lack of integration of report data. This research aims to design a web-based application that is able to manage work visit schedules in a structured manner and facilitate the creation of visit reports digitally. The method used in this study is the Waterfall system development method which includes needs analysis, system design, implementation, and testing. The results of the study show that the application is able to display the visit schedule in real time, minimize schedule conflicts, and speed up the process of preparing work visit reports. Thus, this application makes a significant contribution in increasing the effectiveness and efficiency of the work visit administration process at BAPPELITBANG.